The delinquent girl - Zahn, Margaret A. (Philadelphia, PA : Temple University Press, 2009)
"Over the past decade and a half, girls' involvement in the juvenile justice system has increased. Yet the topic remains understudied by criminologists. The Delinquent Girl is a "state-of-the-field" effort that identifies and analyzes the kinds of crimes that girls commit and the causes of girls' delinquency. The distinguished academics and practitioners who contributed to this volume provide an overview of the research on girls' delinquency, discuss policy implications, and point to areas where further research is critically needed." "The book begins with an examination of the major theories and explanations of female delinquency and considers the "gender gap" between male and female offenders. Other issues, such as the role of the juvenile justice system and changes in justice policies, are also addressed. Throughout The Delinquent Girl, the contributors use criminological and feminist theories to consider causes and implications - e.g., family dysfunction, community factors - and provide insight into treating and preventing juvenile delinquency."--BOOK JACKET.
List of figures and tables -- Introduction / Margaret A Zahn, Robert Agnew, and Angela Browne -- Introduction -- Contribution of "mainstream" theories to the explanation of female delinquency / Robert Agnew -- Feminist theories of girls' delinquency / Jody Miller, Christopher W Mullins -- Trends in girls' delinquency and the gender gap: statistical assessment of diverse sources / Darrell Steffensmeier, Jennifer Schwartz -- Biopsychological factors, gender, and delinquency / Diana Fishbein, Shari Miller, Donna Marie Winn, Gayle Dakof -- Family influences on girls' delinquency / Candace Kruttschnitt, Peggy Giordano -- Peer influences on girls' delinquency / Peggy Giordano -- Girls, schooling, and delinquency / Allison Ann Payne, Denise C Gottfredson, Candace Kruttschnitt -- Gender differences in neighborhood effects and delinquency / Margaret A Zahn, Angela Browne -- Context of girls' violence: peer groups, families, schools, and communities / Merry Morash, Meda Chesney-Lind -- Young women and street gangs / Jody Miller -- Girls in the juvenile justice system / Barry C Feld -- Appendix: Girls study group members -- Notes -- References -- Contributors -- Index.
Includes bibliographical references (p. [273]-324) and index.
Keywords: Female juvenile delinquents; Female juvenile delinquents